Pengaruh Gaya Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kualitas Pelayanan Masyarakat Pada Polres Kota Mamuju - Aqil, Muhammad; S, Ramli; Alamsyah, Alamsyah (Journal of Management Branding, 2024)
This research aims to determine and analyze the influence of transformational leadership style and work discipline partially and simultaneously on service quality at the Mamuju City Police. Determining the sample for this research was carried out using a saturated sampling technique (census), so that the sample used in this research was all personnel/employees at the Mamuju City Police, totaling 72 people. The test results show that partially the variables transformational leadership style and work discipline have a significant positive effect on the quality of service at the Mamuju City Police and simultaneously the variables transformational leadership style and work discipline have a significant positive effect on the quality of service at the City Police.